Recent Origin of a Range-Restricted Species With Subsequent Introgression in its Widespread Congener in the Phyteuma spicatum Group (Campanulaceae) - Larsson, Dennis; Šarhanová, Petra; Paun, Ovidiu; Schneeweiss, Gerald M (Molecular ecology, 2025)
Understanding the causes of restricted geographic distributions is of major interest to evolutionary and conservation biologists. Inferring historical factors has often relied on ad hoc interpretations of genetic data, and hypothesis testing within a statistical framework under different demographic scenarios remains underutilised. Using coalescent modelling on RAD-sequencing data, we (i) test hypotheses about the origin of Phyteuma gallicum (Campanulaceae), a range-restricted endemic of central France sympatric with its widespread congener Ph. spicatum, and (ii) date its origin, irrespective of its mode of origin, to test the hypothesis that the restricted range is due to a recent time of origin. The best supported model of origin is one of a dichotomous split of Ph. gallicum, confirmed as distinct species, and the Central European Ph. nigrum with subsequent gene flow between Ph. gallicum and Ph. spicatum. The split of Ph. gallicum and Ph. nigrum is estimated at 45-55,000 years ago. Coalescent modelling on genomic data not only clarified the mode of origin (dichotomous speciation instead of a previously hypothesised hybridogenic origin) but also identified recency of speciation as a sufficient, although likely not the sole, factor to explain the restricted distribution range. Coalescent modelling strongly improves our understanding of the evolution of range-restricted species that are frequently of conservation concern, as is the case for Ph. gallicum.
Keywords: dichotomous versus hybridogenic origin; Genetic Speciation; France; populační genetika; Genetics, Population; fylogeneze; Sequence Analysis, DNA; Phylogeny; tok genů; sekvenční analýza DNA; Francie; Models, Genetic; vznik druhů (genetika); French massif central; range‐restricted endemics; DNA rostlinná; DNA, Plant; Campanulaceae; modely genetické; phylogeography; coalescent modelling; Gene Flow